2021
DOI: 10.1161/jaha.120.018585
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Blood Pressure Visit‐to‐Visit Variability on Adverse Events in Patients With Nonvalvular Atrial Fibrillation: Subanalysis of the J‐RHYTHM Registry

Abstract: Background Blood pressure (BP) variability has reportedly been a risk factor for various clinical events. To clarify the influence of BP visit‐to‐visit variability on adverse events in patients with nonvalvular atrial fibrillation, a post hoc analysis of the J‐RHYTHM Registry was performed. Methods and Results Of 7406 outpatients with nonvalvular atrial fibrillation from 158 institutions, 7226 (age, 69.7±9.9 years; men, 70.7%), in whom BP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…The risk of baseline HR or HR-end for adverse events in each quartile or group was expressed as hazard ratios or odds ratios (ORs) and 95% confidence intervals (CIs) versus the second quartile. Explanatory variables for multivariable analysis were adopted from well-known risk factors used in our previous subanalyses for hypertension and BP [9] , [10] . These included components of the CHA 2 DS 2 -VASc score (congestive heart failure, hypertension, age ≥ 75 years, diabetes mellitus, history of stroke or TIA, vascular disease [coronary artery disease], age 65–74 years, female sex) [11] , warfarin and antiplatelet use, AF type, and systolic BP-end (BP at the time closest to an event or at the last visit of follow-up) (Model 1).…”
Section: Methodsmentioning
confidence: 99%
“…The risk of baseline HR or HR-end for adverse events in each quartile or group was expressed as hazard ratios or odds ratios (ORs) and 95% confidence intervals (CIs) versus the second quartile. Explanatory variables for multivariable analysis were adopted from well-known risk factors used in our previous subanalyses for hypertension and BP [9] , [10] . These included components of the CHA 2 DS 2 -VASc score (congestive heart failure, hypertension, age ≥ 75 years, diabetes mellitus, history of stroke or TIA, vascular disease [coronary artery disease], age 65–74 years, female sex) [11] , warfarin and antiplatelet use, AF type, and systolic BP-end (BP at the time closest to an event or at the last visit of follow-up) (Model 1).…”
Section: Methodsmentioning
confidence: 99%
“…Other proposed mechanisms, such as demand supply mismatch particularly during stress exercises, disrupted the coronary arteries flow and consequently myocardial ischemia develops which leads to the development of arrhythmias. 23,24 The study showed direct linkage of age and gender on the prevalence and occurrence of cardiac arrhythmias. Males were more prone towards developing cardiac arrhythmias in comparison with the females of age group (<60 years) but there was no such relation after 70 years.…”
Section: Discussionmentioning
confidence: 97%
“…Finally, only baseline BP values were available for the J-RISK AF. The impact of BP values at the time closest to an event, visit-to-visit BP variability, and BP consistency during the follow-up period was evaluated only in the J-RHYTHM Registry, 16 , 17 , 38 in which visit-to-visit BP values were collected.…”
Section: Discussionmentioning
confidence: 99%
“… 16 Furthermore, systolic BP visit-to-visit variability evaluated by standard deviation (SD) was also significantly associated with the incidence of thrombo-embolism, major haemorrhage, and all-cause death independent of BP-end. 17 In contrast, in the Fushimi AF Registry, a baseline systolic BP ≥150 mmHg was associated with a higher incidence of stroke/systemic embolism, haemorrhagic stroke, and major bleeding. 18 …”
Section: Introductionmentioning
confidence: 93%